Uniform convergence of numerical conformal mappings of interior domains in the charge simulation method - Tetsuo Inoue (International Journal of Mathematics and Mathematical Sciences)
The uniform convergence of the approximations by new numerical schemes in the charge simulation method, which have been recently proposed by Inoue (1997), will be studied. The exponential decrease of the errors will also be shown.